Evidence of Development Impact from Institutional Change : A Review of the Evidence on Open Budgeting - Ling, Cristina (World Bank Group, Washington, DC, 2014)
Despite the growing body of literature examining the effectiveness of transparency and accountability initiatives, there remains limited substantiation for whether and how open budgeting contributes to reductions in poverty and improvements in the lives of the poor. This paper reviews available evidence and conclude that institutional changes can contribute to higher-level outcomes in certain contexts. The approach first draws from existing studies of transparency and accountability initiatives and then follows their references to broaden the evidence base. The findings highlight the importance of measuring budget transparency, accountability, and participation and tracing their outcomes along an incremental, nonlinear results chain. Logical links or ongoing loops in this sequence include the interplay or interdependency among these three dimensions; the subsequent achievement of key, often mutually reinforcing, intermediate development outcomes; and ultimately, improved program or service delivery as the key lever for influencing development impact. Rather than establishing standard indicators, the process begins to identify which aspects of the institutional change are valid for measurement and what contextual factors to consider. Overall, this review serves as a starting point and underscores the need for further investigation to establish effective measurement practices of institutional change and build an evidence base for understanding the relative robustness of institutional change paths and the context in which they are likely to matter.